The effect of sex on suicide risk during and after psychiatric inpatient care in 12 countries—An ecological study. Issue 1 (2020) - Listabarth, Stephan; Vyssoki, Benjamin; Glahn, Alexander; Gmeiner, Andrea; Pruckner, Nathalie; Vyssoki, Sandra; Wippel, Andreas; Waldhoer, Thomas; König, Daniel
Abstract: Background: Suicide risk in patients is markedly elevated during psychiatric inpatient care, as well as after discharge. However, it is unclear whether, and to what extent, this increased suicide risk varies between sex. Thus, the aim of this study was to analyze sex differences for suicides during and after psychiatric hospitalization in various countries. Methods: National suicide mortality rates and inpatient-related suicide rates (three intervals: during psychiatric inpatient treatment, 1 month, and 1 year after discharge) from 12 countries for 2000–2016 were analyzed, and a logistic model was used to quantify the effect of sex. Results: Persons admitted to or discharged from psychiatric inpatient care exhibited significantly increased rates of suicide compared to those in the general population. Furthermore, increase of suicide risk was significantly higher for females than for males for all investigated time intervals (inpatient suicide odds ratio [OR] 1.85; suicide within 1 month after discharge—OR 1.94; suicide within 1 year after discharge—OR 2.04). Conclusion: Analysis confirmed the time during and after psychiatric inpatient care to be significantly associated with an elevated risk for suicide. Further, a significant sex effect was observed, with females in this population being at a proportionally higher risk for suicide during psychiatric inpatient treatment as well as the year following discharge. Our study implicates that more effective suicide preventive measures during inpatient stay, focusing on female patients, are needed.